How risky is college investment? - Lutz Hendricks; Oksana Leukhina (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
This paper is motivated by the fact that nearly half of U.S. college students drop out without earning a bachelor's degree. Its objective is to quantify how much uncertainty college entrants face about their graduation outcomes. To do so, we develop a quantitative model of college choice. The innovation is to model in detail how students progress towards a college degree. The model is calibrated using transcript and financial data. We find that more than half of college entrants can predict whether they will graduate with at least 80% probability. As a result, stylized policies that insure students against the financial risks associated with uncertain graduation have little value for the majority of college entrants.
urn:nbn:de:hebis:30:3-370162
Keywords: E24; J24; I21; 330; Education; College dropout risk